Apakah Kualitas Produk dan Lokasi Usaha Berpengaruh terhadap Keputusan Pembelian Konsumen pada UMKM Bidang Kuliner? - asmi, asmi; Ahmad, Muhammad Ihsan Said; Nurdiana, Nurdiana; Mustari, Mustari; Tahir, Thamrin (Universitas Negeri Semarang, 2021)
The purpose of this study was to analyze whether product quality and location in the Culinary Sector UKM in Simbang District, Maros Regency, influenced consumer purchasing decisions. This research includes quantitative descriptive research. The population in this study were 3,939 residents of Simbang District aged 20 to 39 years who were registered at the BPS Maros Regency, and samples were taken from 97 culinary business consumers in six villages in Simbang District. Data were collected by questionnaire. Data were analyzed by descriptive statistical analysis and multiple linear regression. The results showed that (1) product quality had a positive and significant effect on consumer purchasing decisions in the Culinary Sector MSMEs in Simbang District, Maros Regency, (2) business location had a positive and significant impact on consumer purchasing decisions on the Culinary Sector MSMEs in Simbang District, Maros Regency, (3) product quality and business location together have a positive and significant impact on consumer purchasing decisions in the Culinary Sector MSMEs in Simbang District, Maros Regency.